Synthesis and Mechanical Response of NiTi SMA Nanoparticle Reinforced Mg Composites Synthesized through Microwave Sintering Process. (2018) - Wakeel, Saif; Manakari, Vyasaraj; Parande, Gururaj; Suchita Kujur, Milli; Ahmad khan, Ateeb; Gupta, Manoj
Abstract: The concept of developing intelligent Self-Healing Metallic Materials that can repair its damage is always fascinating and is of great interest in order to improve the quality service life of engineering components. Due to their low density, magnesium (Mg) and its alloys offer a combination of better specific strength (σ/ρ), damping characteristics and impact resistance and can suit best for the quest of intelligent self-healing materials development. In the current study, Mg is reinforced with 2 wt.% NiTi shape memory alloy (SMA) nanoparticles and the SMA particle effect on the mechanical properties and microstructural evolution of monolithic magnesium are studied. A near dense Mg-2 wt. % NiTi nanocomposite was obtained during the study. The addition of NiTi nanoparticle resulted in a ∼29 % and ∼73% enhancement in the microhardness and grain size of pure Mg. Damping capacity and loss rate of pure Mg also had a superior enhancement of ∼119% and ∼2.6 times, respectively due to the presence of NiTi nanoparticle. The compressive strength properties also exhibited a visible enhancement due to the presence of NiTi nanoparticle without compromising on the fracture strain of the material.